2018
DOI: 10.1159/000488343
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Traumatic Brain Injury Results in Cognitive Deficits Associated with Impaired Endoplasmic Reticulum Stress and Early Tauopathy

Abstract: The leading cause of death in the juvenile population is trauma, and in particular neurotrauma. The juvenile brain response to neurotrauma is not completely understood. Endoplasmic reticulum (ER) stress has been shown to contribute to injury expansion and behavioral deficits in adult rodents and furthermore has been seen in adult postmortem human brains diagnosed with chronic traumatic encephalopathy. Whether endoplasmic reticulum stress is increased in juveniles with traumatic brain injury (TBI) is poorly del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Reiner and colleagues 2014 reported that Novel CB2 Inverse Agonist SMM-189 reduce motor, visual, and emotional deficits after closed-head mild traumatic brain injury mouse model via mitigation of microglial inflammatory action [ 28 ]. ER stress was found to be increased early in juvenile rats exposed to TBI and that these rats developed tau oligomers over the course of 30 days and had significant short-term and spatial memory deficits following injury [ 29 ]. Treangen and colleagues suggested that acute bacterial dysbiosis within the gut microbiome was observed after TBI post-injury in mice [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reiner and colleagues 2014 reported that Novel CB2 Inverse Agonist SMM-189 reduce motor, visual, and emotional deficits after closed-head mild traumatic brain injury mouse model via mitigation of microglial inflammatory action [ 28 ]. ER stress was found to be increased early in juvenile rats exposed to TBI and that these rats developed tau oligomers over the course of 30 days and had significant short-term and spatial memory deficits following injury [ 29 ]. Treangen and colleagues suggested that acute bacterial dysbiosis within the gut microbiome was observed after TBI post-injury in mice [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In-vivo CCI in juvenile rats leads to upregulation of binding immunoglobulin protein (BiP) and C/EBP homologous protein (CHOP) as early as 4 h. After 72 h, there was increased expression of hypoxia-inducible factor (HIF)-1α. In the first case, this indicates an increased load on the endoplasmic reticulum, in the second case, a delayed onset of tissue hypoxia [ 33 ]. After an in-vivo blast-type TBI in rats, there is diffuse microvasculature damage and axonal injury with reactive gliosis, in the absence of macroscopic lesions such as brain edema.…”
Section: Discussionmentioning
confidence: 99%
“…Tau oligomers measured by R23 were significantly increased by 30 days following TBI. The biochemical changes following TBI were associated with increased impulsive-like or anti-anxiety behavior measured with the elevated plus maze, deficits in short-term memory measured with novel object recognition and deficits in spatial memory measured with the Morris water maze in juvenile rats exposed to TBI [ 20 ].…”
Section: Executive Functionsmentioning
confidence: 99%